THE TEACHER AND STUDENTS’ TALKS IN ENGLISH FOR YOUNG LEARNERS’ CLASSROOM SITUATION - Febi Saputra; Sukma Septian Nasution; Nur Najibah Sukmawati (Lexeme : Journal of Linguistics and Applied Linguistics, 2021)
The objective of study is to identify and describe the types of talks practiced by a teacher and her students in an English class. This is a descriptive qualitative study that observed a classroom instructional practices involving a teacher and 30 students at a private Elementary school in Indonesia. The data were obtained through instructional practices recorded and posted in a Youtube Channel with introducing animals as the topic of the meeting. The obtained data were then analyzed by using Flender’s Interaction Analysis Categories (FIAC) that focuses on types of talks between a teacher and students. The steps like transcribing, coding, and analyzing the findings were interpreted in descriptive form. The finding shows that every type of talks was practiced by the teacher and the students. On the types of the talks, it was revealed that asking question, giving direction, and praises or encourages are the most frequently-used types by the teacher and on the types of students’ talks, giving response, silence or confuse were dominant. These types of talks conclude good interactions between the teacher and students particularly on the types of talks that are they used. Through this study, the writer wish that can useful in giving a contribution in English classroom interaction.